Research progress of biomarkers in the prediction of anti-PD-1/PD-L1 immunotherapeutic efficiency in lung cancer - Wang, Luyao; Yang, Zongxing; Guo, Fucheng; Chen, Yurong; Wei, Jiarui; Dai, Xiangpeng; Zhang, Xiaoling (Frontiers in Immunology, 2023)
Currently, anti-PD-1/PD-L1 immunotherapy using immune checkpoint inhibitors is widely used in the treatment of multiple cancer types including lung cancer, which is a leading cause of cancer death in the world. However, only limited proportion of lung cancer patients will benefit from anti-PD-1/PD-L1 therapy. Therefore, it is of importance to predict the response to immunotherapy for the precision treatment of patients. Although the expression of PD-L1 and tumor mutation burden (TMB) are commonly used to predict the clinical response of anti-PD-1/PD-L1 therapy. Other factors such as tumor specific genes, dMMR/MSI and gut microbiome are also promising predictors for immunotherapy in lung cancer. Furthermore, the invasive peripheral blood biomarkers including blood DNA-related biomarkers (e.g., ctDNA, bTMB), blood cell-related biomarkers (e.g., immune cells, TCR) and other blood-related biomarkers (e.g., soluble PD-L1, cytokines) were utilized to predict the immunotherapeutic response. In this review, the current achievements of anti-PD-1/PD-L1 therapy and the potential biomarkers for the prediction of anti-PD-1/PD-L1 immunotherapy in lung cancer treatment were summarized and discussed.